2022
DOI: 10.3389/fimmu.2022.907481
|View full text |Cite
|
Sign up to set email alerts
|

Mining of Marburg Virus Proteome for Designing an Epitope-Based Vaccine

Abstract: Marburg virus (MARV) is one of the most harmful zoonotic viruses with deadly effects on both humans and nonhuman primates. Because of its severe outbreaks with a high rate of fatality, the world health organization put it as a risk group 4 pathogen and focused on the urgent need for the development of effective solutions against that virus. However, up to date, there is no effective vaccine against MARV in the market. In the current study, the complete proteome of MARV (seven proteins) was analyzed for the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…Both MM_GBSA and MM_PBSA binding energy calculations for respective docked and molecular dynamics complexes illustrated the predominance of electrostatic potentials and polar residue energy contributions for the vaccine towards the TLR site. Greater electrostatic negative values, suggesting stronger binding affinities, were consistent with reported results of other research groups investigating vaccines of other microorganism origins towards different TLRs, including our investigated ones TLR4 and TLR2 (Dar et al, 2019;Soltan et al, 2022a). It is worth noting that, the here simulated vaccine was in dynamic motion at the TLRs interface the thing which is consistent with the reported thermodynamic behavior of various protein-protein complexes (Zhang et al, 2016;Zhang and Buck, 2017;Sami et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both MM_GBSA and MM_PBSA binding energy calculations for respective docked and molecular dynamics complexes illustrated the predominance of electrostatic potentials and polar residue energy contributions for the vaccine towards the TLR site. Greater electrostatic negative values, suggesting stronger binding affinities, were consistent with reported results of other research groups investigating vaccines of other microorganism origins towards different TLRs, including our investigated ones TLR4 and TLR2 (Dar et al, 2019;Soltan et al, 2022a). It is worth noting that, the here simulated vaccine was in dynamic motion at the TLRs interface the thing which is consistent with the reported thermodynamic behavior of various protein-protein complexes (Zhang et al, 2016;Zhang and Buck, 2017;Sami et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, TLR exists at the stage before downstream signal transduction in the C-shaped horse-shoe architecture (Park et al, 2009;Ohto et al, 2012). The inner concave surface of TLRs has been successfully investigated within current literature as the stable interface for different multi-epitope vaccines targeting different types of microbial organisms (Soltan et al, 2021;2022a;Cuscino et al, 2022). Focusing on vaccines targeting K. Pneumoniae, Dar et al reported successful affinity for their immunoinformatics-designed multiepitope vaccine towards the inner concave interfaces of both TLR4 and TLR2 (Dar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Such a subunit (recombinant) vaccine platform can thereby help in developing multivalent vaccine candidates for protecting against filoviruses while retaining their safety and efficacy (Lehrer et al 2021). Few other vaccines being tried include multi-epitope vaccine, proteomebased vaccine exploiting computational methods, virus-like particles (VLP), adenoviral vector-based multi-filovirus vaccine, rprotein based filovirus multivalent vaccine, and rVSV-based vesiculovax vector vaccine (rVSV-N4CT1-MARV-GP), and efforts are being made for effective platform designing of preventive MVD vaccines (Reynolds and Marzi 2017;Hasan et al 2019;Suschak and Schmaljohn 2019;Dulin et al 2021;Lehrer et al 2021;Sami et al 2021;Longini et al 2022;Sebastian et al 2020;Soltan et al 2022;Woolsey et al 2022;Zhao et al 2022). Another candidate vaccine (recombinant VSV/ rVSV-based) known as PHV01 has been tested in the guinea pig model for confirming the efficacy (protective effects) against MVD (Zhu et al 2022).…”
Section: Treatment and Vaccinesmentioning
confidence: 99%
“…However, there are a group of antivirals under development against the virus such as Galidesivir–BCX4430, Favipiravir–T-705, Remdesivir and Polyclonal concentrated IgG, which might protect against the disease (Kortepeter et al 2020 ). Some of the promising vaccine platforms being utilized for developing MVD vaccines comprise of recombinant (r) vesicular stomatitis virus (VSV) vector MARV vaccine (rVSVΔG-MARV-GP), multi-epitope vaccine using vaccinomics and immunoinformatics approaches, proteome based designing of an epitope-based vaccine using computational approach, virus-like particles (VLP), replication-deficient simian adenoviral vector-based multi-filovirus vaccine, r-protein based filovirus multivalent vaccine, and rVSV-based vesiculovax vector based vaccine (rVSV-N4CT1-MARV-GP) (Hasan et al 2019 ; Suschak and Schmaljohn 2019 ; Sebastian et al 2020 ; Dulin et al 2021 ; Lehrer et al 2021 ; Sami et al 2021 ; Abir et al 2022 ; Soltan et al 2022 ; Woolsey et al 2022 ; Zhao et al 2022 ). In May 2020, the European Medicine agency (EMA) granted a marketing authorization to Zabdeno (Ad26.ZEBOV) and Mvabea (MVA-BN-Filo) against Ebola.…”
mentioning
confidence: 99%
“…MARV is a risk group 4 pathogen due to highly contagious nature and high CFR, therefore there is an urgent need to develop effective solutions against this deadly virus before it expands out widely from Africa to other countries (Soltan et al 2022 ; Zhao et al 2022 ). MVD has been considered a neglected infectious disease, which has resulted into small outbreaks from time to time in past five decades, large outbreaks have been rare.…”
mentioning
confidence: 99%